Modifying the shoulder joint position during shrugging and retraction exercises alters the activation of the medial scapular muscles. (February 2016) - Castelein, Birgit; Cools, Ann; Parlevliet, Thierry; Cagnie, Barbara
Abstract: Background: In patients with shoulder or neck pain, often an imbalance of the activation in the scapular upward and downward rotators is present which can cause abnormalities in coordinated scapular rotation. Shrug exercises are often recommended to activate muscles that produce upward rotation, but little information is available on the activity of the downward rotators during shrugging exercises. The position used for the shrug exercise may affect the relative participation of the medial scapular rotators. Objectives: To compare muscle activity, using both surface and fine-wire electrodes, of the medial scapular muscles during different shoulder joint positions while performing shrug and retraction exercises. Design: Controlled laboratory study. Method: Twenty-six subjects performed 3 different exercises: shrug with the arms at the side while holding a weight ("Shrug"), shrug with arms overhead and retraction with arms overhead. EMG data with surface and fine wire electrodes was collected from the Upper Trapezius (UT), Levator Scapulae (LS), Middle Trapezius (MT), Rhomboid Major (RM) and Lower Trapezius (LT). Results: The results showed that activity levels of the main medial scapular muscles depend upon the specific shoulder joint position when performing shrug and retraction exercises. High UT activity was found across all exercises, with no significant differences in UT activity between the exercises. The LS and RM activity was significantly lower during "ShrugOverhead" and the RM, MT and LT activity was significantly higher during "RetractionOverhead". Conclusions: This study has identified that all three exercises elicited similar UT activity. LS and RM activity is decreased with the "ShrugOverhead" exercise. The "RetractionOverhead" was the most effective exercise in activating the medial scapular muscles. Highlights: Modifying a shrug can alter balance between scapular upward and downward rotators. "Shrug", "ShrugOverhead" and "RetractionOverhead" elicited similar UT activity. The lowest activity of the downward rotators was during "ShrugOverhead". The "RetractionOverhead" was most effective in activating medial scapular muscles.